The Influence of IDWG Improvement of Hypotension Events in Hemodialized Patients in Rasyida Hospital Medan - Juliana Dewi; Febriantoni; Juliana Dewi; Katiti; M Aryandra Hasibuan; Tiarnida (Institute of Computer Science (IOCS), 2020)
Kidney failure is a condition in which the loss of the ability of the kidneys to filter fluids and food scraps, when these conditions occur levels of toxins and harmful liquids will accumulate in the body. One treatment for kidney failure is hemodialysis. Hemodialysis is a therapy that is carried out if the condition of the kidneys is unable to function or has malfunction up to values ​​below 15 ml / min / 1.73. Although hemodialysis is safe and beneficial for patients, it does not mean that it has no side effects. An increase in body weight between the two hemodialysis IDWG (Interdialytic Weight Gain) times is a frequent side effect, one of which is intradialysis hypotension. Objective: to identify the effect of increasing IDWG on the incidence of hypotension in hemodialysis patients at the Rasyida Kidney Hospital in Medan. Method: quantitative research design with analytic survey through a cross sectional approach. The population in this study were all patients with chronic kidney failure who did hemodialysis at the Rasyida Kidney Hospital in Medan. The sample in this study amounted to 22 respondents. Patients will be measured body weight and blood pressure. Measurements were made before and after hemodialysis at visits I, II and III. Results: The majority of hemodialysis patients in Medan Rasyida Kidney Special Hospital were> 50 years (50%), and 50% were male and 50% female, 50% of patients experienced hypotension and increased IDWG. The results of bivariate chi square can be p-value 0,000. So, it can be concluded that there is an effect of increasing IDWG on the incidence of hypotension in hemodialysis patients.